Determinan Minat Profesi Dibidang Perpajakan - Nugroho, Paskah Ika; Priskila, Leonita (Ultimaccounting Jurnal Ilmu Akuntansi, 2018)
The purpose of this study is to evaluate the influence of economic motivation and perception about taxes, and tax brevet towards the interest in the field of taxation. Data collection was done through the distribution of questionnaires to the Accounting undergraduate students who were taking taxation laboratory courses at Universitas Kristen Satya Wacana. Sample selection technique was done by purposive sampling. Samples are 100 students consisting of 50 students who follow the tax brevet and 50 students who do not follow the tax brevet. Multiple linear regressions are used for data analysis using SPSS 2.0 application. The results of this study show that the economic motivation of Students of Economics and Business Faculty of Accounting Study Program of Universitas Kristen Satya Wacana affect the interest in the field of taxation profession. Perception about taxes by the students of Economics and Business Faculty of Universitas Kristen Satya Wacana of Accounting Program Study affect the interests in the field of taxation profession. Perception of tax brevet by the students of Economics and Business Faculty of Accounting Study Program of Satya Wacana Christian University influence the interests in the field of taxation.